2007
DOI: 10.1080/10810730601152771
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Social Undermining as Correlates for Alcohol, Drug, and Mental Disorders in American Indian Women Presenting for Primary Care at an Indian Health Service Hospital

Abstract: The purpose of this study was to determine the relationship of two types of social support (emotional and instrumental) and two types of social undermining (critical appraisal and isolation) with five categories of alcohol, drug, or mental disorders (ADM; any mood, any anxiety, any substance abuse, any disorder, and two or more disorders) in 169 American Indian women presenting for primary care at an Indian Health Service facility. Social support and social undermining are often treated as opposite poles, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 53 publications
2
35
0
2
Order By: Relevance
“…The operationalization of emotional support in this study includes provision of love, affirmation, and caring, whereas instrumental support contains tangible aid. This choice is consistent with prior research examining health outcomes (e.g., Oetzel, Duran, Jiang, & Lucero, 2007). We also considered two types of social support from health care providers: information and emotional support (Galassi, Schanberg, & Ware, 1992).…”
Section: Social Support and Social Underminingmentioning
confidence: 88%
See 1 more Smart Citation
“…The operationalization of emotional support in this study includes provision of love, affirmation, and caring, whereas instrumental support contains tangible aid. This choice is consistent with prior research examining health outcomes (e.g., Oetzel, Duran, Jiang, & Lucero, 2007). We also considered two types of social support from health care providers: information and emotional support (Galassi, Schanberg, & Ware, 1992).…”
Section: Social Support and Social Underminingmentioning
confidence: 88%
“…direct effects for undermining (e.g., Jia et al, 2005;Oetzel et al, 2007). For example, in a cross-sectional survey of 86 participants living with HIV, Viswanathan and colleagues (2005) found that social support was positively related to the physical component summary of the MOS-HIV in a model that considered demographics, CD4 cell count, and medication adherence.…”
mentioning
confidence: 96%
“…Social support and undermining were measured with a modified version of a previously validated social support and undermining scale (Oetzel et al, 2007). There are 20 items measured on a five-point scale (5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to social support, PLWH's experiences of negative interpersonal interactions, also known as social undermining (Finch, 1998;Fleishman et al, 2000;Oetzel, Duran, Jiang, & Lucero, 2007;Oetzel et al, 2014), have received limited scholarly attention. Social undermining negatively impacts behavioral health, including drug and mood disorders (e.g., Axelrod, Myers, Durvasula, Wyatt, & Cheng, 1999;Finch, 1998;Oetzel et al, 2007).…”
Section: Social Underminingmentioning
confidence: 96%
See 1 more Smart Citation